A spatial decision support system for municipal solid waste landfill sites (case study The Mazandaran Province, Iran) - Amirsoleymani, Yasaman (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
Landfilling is an inevitable step for the municipal solid waste (MSW) management system in developing countries. This article presents a Spatial Decision Support System (SDSS) that was developed for the monitoring of municipal landfills and siting the new places for waste disposal at Mazandaran province, south of Caspian Sea, Iran. The effective criteria and evaluation constraints were chosen according to the Iran waste management law. The ArcGIS 10.4.1 software was used for creating a geospatial database and the analytic hierarchy process (AHP) was used for ranking the criteria. By integrating the criteria, a suitability map was generated into four categories: high suitability, moderate suitability, low suitability and illegal areas. Using ArcGIS online, the maps were shared on a website that was specifically designed for this purpose. The decision-makers can check online the laws, the effective criteria and the results of spatial analysis for optimal siting. Also, the results of environmental evaluations for active landfills have been provided. Given the characteristics of active landfills and the optimal sites for the possible development, the SDSS can provide a mutually beneficial relationship between the experts, decision-makers and stakeholders to decide about the priority of actions required for the relocation of landfills, site closure or emergency care